Evaluation of the quality of CT images acquired with the single energy metal artifact reduction (SEMAR) algorithm in patients with hip and dental prostheses and aneurysm embolization coils - Sonoda, Akinaga; Nitta, Norihisa; Ushio, Noritoshi; Nagatani, Yukihiro; Okumura, Noriaki; Otani, Hideji; Murata, Kiyoshi (Japanese journal of radiology, 2015)
Purpose We compared the quality of the images acquired with single energy metal artifact reduction (SEMAR) on CT scans of three different human body areas. Materials and methods Our institutional review board approved the study protocol. CT studies of 58 patients (hip prosthesis, n = 20; iliac artery aneurysm embolization, n = 20; dental prosthesis, n = 18) were retrospectively reconstructed using interactive reconstruction (IR) and IR plus SEMAR. Two radiologists independently evaluated the images for the reduction of metal artifacts at three sites, i.e., 0–1, 1–5, and 5–10 cm from their edges, and recorded their findings on a 100-mm-long line that corresponded to the Likert scale and ranged from 0 (invisible) to 100 mm (clearly visible). The standard deviation in Hounsfield units was used as the noise assessment tool. Statistical analysis was performed with the t test and the Wilcoxon signed-rank test. Results The image quality of scans of hip prostheses and metal embolization coils was significantly improved when SEMAR was used ( p < 0.05). On scans of dental prostheses, SEMAR did not contribute significantly, especially in the area 1 cm from the edge of the implant. Conclusion Visual subjective evaluation showed that SEMAR improved the image quality.